PERAN WANITA SINGLE PARENTDALAM MENJALANKAN FUNGSI KELUARGA PADA KARYAWAN PT. ISS MALL PEKANBARU KOTA PEKANBARU - Hutauruk, Meilani; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Being a parent is one of the many tasks humans as social beings. Integrity of the parents ( father and mother) in a family is needed to help children to have self-development. But there are also families that is less complete, ie that only a family headed by a woman (the mother) only. This can happen due to many reason, among others due to divorce, widowed by her husband due to his own choice or. This phenomenon is often referred to as a single parent. Certainly not easy being a single parent, because he had to act as father and mother to her children. This study aims to determine how the role of women in a single parent family function with variety of problems faced and the strategies undertaken by the female single parent to tackle the problem.Based on the fact that some women who become single parents often prefer not to marry again and more focused on taking care of her children. Being a single parent for a mother more difficulty and severity of dual task as breadwinners and care of children. It takes an uphill battle to raise children, including meeting the needs of family life. Not to mention people's views about the family, the single parent so women should be able to position themselves well for a family or for society.Keywords: Roles, Single Parent, Family Function